Formation of Continental Crust by Diapiric Melting of Recycled Crustal Materials in the Mantle Wedge - Shi‐Min Li; Qing Wang; Di‐Cheng Zhu; Peter A. Cawood; Robert J. Stern; Zhidan Zhao (Geophysical Research Letters)
Abstract The compositional similarity between high‐Mg andesite‐dacite from accretionary orogens and bulk continental crust (CC) provides an opportunity to unravel the CC formation paradox. Compositional data from a global compilation of Quaternary magmatic arcs indicate the presence of low‐Mg series (LMS) and high‐Mg series (HMS). The LMS show trends of crystal fractionation and can be subdivided into high Ba/Th and high La/Sm groups, which likely originate from fluid‐ and sediment melt‐modified mantle wedge, respectively. In contrast, the HMS have variably mixed compositions (e.g., high Mg#, Ba/Th, and La/Sm) and can be explained by partial melting of mélange diapirs rising into the mantle wedge, which are mixtures of subducted sediment, eroded arc crust or CC, buoyant oceanic crust, and peridotite. We, therefore, propose a two‐step process for creating CC involving extraction of LMS from the mantle followed by re‐melting of recycled LMS in the mantle to generate HMS and thus CC.